2018
DOI: 10.1039/c8dt01582a
|View full text |Cite
|
Sign up to set email alerts
|

Ferrocifens labelled with an infrared rhenium tricarbonyl tag: synthesis, antiproliferative activity, quantification and nano IR mapping in cancer cells

Abstract: Antiproliferative activities of several members of the ferrocifen family, both in vitro and in vivo, are well documented although their precise location in cancer cells has not yet been elucidated. However, two different infrared imaging techniques have been used to map the non-cytotoxic cyrhetrenyl analogue of ferrociphenol in a single cell. This observation prompted us to tag two ferrocifens with a cyrhetrenyl unit [CpRe(CO)3; Cp = η5-cyclopentadienyl] by grafting it, via an ester bond, either to one of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 35 publications
2
20
0
Order By: Relevance
“…Previous multimodal optical imaging studies of arhenium-(I) carbonyl derivative of mestranol in MDB-MB-231 cells showed preferential accumulation in another highly membranous organelle namely,t he golgi apparatus, [15] while recently,amixed ferrocenyl/ rhenium(I) carbonyl tamoxifen derivative was located, by nano-IR imaging,m ainly in the nucleus of MDA-MB-231 cells. [16] This contrasts dramatically with the cellular distribution of another anticancer cationic half-sandwich Os(II) complex, which was found mainly located in the mitochondria by the same nanoimaging technique and cellular fractionation coupled to inductively coupled plasma-mass spectrometry (ICP-MS) analysis. [11] Chemically fixed cells were further analyzed by 3D X-ray fluorescence nanoimaging.W hile 2D-XRF imaging informs on the projected elemental distribution across the cell thickness,3 DX RF provides depth information and discriminates between intracellular,s urface and extracellular locations of elements (both endogenous and exogenous).…”
mentioning
confidence: 94%
“…Previous multimodal optical imaging studies of arhenium-(I) carbonyl derivative of mestranol in MDB-MB-231 cells showed preferential accumulation in another highly membranous organelle namely,t he golgi apparatus, [15] while recently,amixed ferrocenyl/ rhenium(I) carbonyl tamoxifen derivative was located, by nano-IR imaging,m ainly in the nucleus of MDA-MB-231 cells. [16] This contrasts dramatically with the cellular distribution of another anticancer cationic half-sandwich Os(II) complex, which was found mainly located in the mitochondria by the same nanoimaging technique and cellular fractionation coupled to inductively coupled plasma-mass spectrometry (ICP-MS) analysis. [11] Chemically fixed cells were further analyzed by 3D X-ray fluorescence nanoimaging.W hile 2D-XRF imaging informs on the projected elemental distribution across the cell thickness,3 DX RF provides depth information and discriminates between intracellular,s urface and extracellular locations of elements (both endogenous and exogenous).…”
mentioning
confidence: 94%
“…Previous multimodal optical imaging studies of a rhenium(I) carbonyl derivative of mestranol in MDB‐MB‐231 cells showed preferential accumulation in another highly membranous organelle namely, the golgi apparatus, while recently, a mixed ferrocenyl/ rhenium(I) carbonyl tamoxifen derivative was located, by nano‐IR imaging, mainly in the nucleus of MDA‐MB‐231 cells . This contrasts dramatically with the cellular distribution of another anticancer cationic half‐sandwich Os(II) complex, which was found mainly located in the mitochondria by the same nanoimaging technique and cellular fractionation coupled to inductively coupled plasma‐mass spectrometry (ICP‐MS) analysis …”
Section: Figurementioning
confidence: 85%
“…These CPPs can be used to transport various hydrophobic anticancer drugs such as promising organometallic molecules: ferrocifen which combine hydroxytamoxifen and ferrocene together 10,11 . They present major properties as stability in non-oxidative environment, reversible oxidation-reduction (redox) potential, and impressive antiproliferative effects on various cancer cells [12][13][14] . The action mechanism of ferrocifens can be related to the oxidation state of iron in the ferrocene moiety.…”
Section: Toc Graphic Abstractmentioning
confidence: 99%